Incentives and the Diffusion of Agricultural Knowledge: Experimental Evidence from Northern Uganda. (14th May 2019) - Shikuku, Kelvin Mashisia; Pieters, Janneke; Bulte, Erwin; Läderach, Peter
Abstract: We present results of a randomized evaluation that assesses the effects of different incentives for diffusion of agricultural knowledge by smallholders in northern Uganda. Randomly-selected disseminating farmers (DFs) from a large sample of villages are assigned to one of three experimental arms: ( a ) training about climate smart agriculture, ( b ) training plus a material reward for knowledge diffusion, and ( c ) training plus a reputational gain for knowledge diffusion. We find that leveraging somebody's reputation (or social recognition) has a positive impact on DFs' experimentation and diffusion effort. This impact is stronger than that measured in the private material rewards treatment.